SEJARAH MADZHAB TAFSIR; TELAAH PERKEMBANGAN TAFSIR SUSATRA - Lidia Nur Eka hidayat (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
Literary interpretation as one of the treasures of interpretation that brings fresh air in interpreting the Koran. If in general the interpretation of the Qur'an is considered contextual and seems too rigid, then the literary interpretation breaks this statement. This style of interpretation processes the literature contained in the Qur'an and relates it to the reality of contemporary society. This article uses literature review by collecting several studies of figures in it. The results of the research in this article are that the fluctuation of interpretation using the aqli method has developed since the third century of the Hijri. The dimension of interpretation has shifted from the previous impression of being contextual to being more easily understood. In addition, several styles of interpretation provide a solutive interpretation of complex human problems. One of them is the literary interpretation carried by Amin Al-Khuli. Amin Al-Khuli places the Qur'an as the greatest book of literature while interpreting it with a method